Existential Isolation in Whisky (2004), reading Uruguayan cinema beyond the concept of small cinema - Lopes Gemelli, Cesar (Revista PHILIA | Filosofia, Literatura & Arte, 2019)
The Cinematography in Whisky (2004) is essential in the directors’ efforts to explore existential isolation. The incompleteness of knowledge, the uncrossable gaps between people, and the impossibility of communion among individuals are some of the themes explored in this film, directed by Juan Pablo Rebella and Pablo Stoll. These are mostly absent in the scholarship about the movie, which tends to focus on the concept of small cinema. The present text aims to build on these discussions to propose a reading of Whisky as a work of art that, although made within a very specific context of production, is not limited by it. Keywords: Cinematography. Uruguayan cinema. Small cinema.